Evaluasi Status Kesuburan Tanah pada Lahan Tanaman Nilam di Desa Karya Mulya Kecamatan Kulisusu Barat Kabupaten Buton Utara - Azza, Radi Khairul; Ginting, Sahta; Resman, Resman; Darwis, Darwis; Alam, Syamsu; Namriah, Namriah (Jurnal Agroteknologi (Agronu), 2025)
Soil fertility is the ability of the soil to provide nutrients in balanced amounts for plant growth and production. Land cultivated for agriculture has varying levels of fertility. Proper soil management is an important factor in determining the growth and yield of cultivated plants. This study aims to describe the status of soil fertility and recommend the direction of fertilization for patchouli plants in Karya Mulya Village, West Kulisusu, North Buton. This research was conducted from December 2022 to February 2023. The method used in this study was a free survey method based on the location of the patchouli plantation. Sampling was carried out at a depth of 0-20 cm. The samples taken were analyzed in the laboratory to assess pH, organic C, available P, available K, CEC, and KB. The results of the study showed that the pH was classified as slightly acidic with a value of 6.1-6.3, low to moderate organic C with a value of 1.04-1.58%, low available P with a value of 5.98-7.59 ppm, low to moderate available K with a value of 0.29-0.42 me 100 g⁻¹, medium and high CEC with a value of 19.74-25.23 me 100 g⁻¹, low to moderate KB with a value of 38.68-43.61%. Based on the results of the assessment of soil chemical properties, it can be concluded that the level of soil fertility at the research location is low. Fertilization efforts are needed to increase the fertility of patchouli planting soil by paying attention to the right aspects in fertilization.